An analysis of the factors influencing the supply of private label brands by National Brand Manufacturers in Kenya - Chotaliya, Bhavika Chandrakant (Strathmore University, 2016)
Kenyan supermarket retailers are expanding their product portfolio by outsourcing store brands to local manufacturers under their design and specifications in a phenomenon known as Private Label Brands (PLB). Research on this subject reveals that this new trend is posing a threat to National Brand (NB) manufacturers due to the remarkable growth of PLB and favorable consumer response. However, research from the manufacturer’s perspective and the growth of the PLB concept has received limited global attention with no available studies on the Kenyan market. This study rationally examines economic, strategic and market factors, influencing the supply of Private Label Brands by the National Brand manufacturers with an aim of recommending win-win strategies for the stakeholders. The study used a descriptive survey design characterized by a systematic collection of data from respondents through questionnaires. The collected data is analyzed using factor analysis technique, correlation, and hypothesis tests. The three categories of factors had an influence on the supply of PLB with the cost of production, negotiation and bargaining power and shelf space allocation emerged as prominent sub factors. The empirical study confirms the existence of a strong relationship between the Kenyan retailer and manufacturer; nevertheless, pricing and low volumes were perceived as constraints. This study is limited by only three factors namely: economic, market and strategic paving way for an in-depth analysis of other factors existing in the Kenyan market.
Submitted in partial fulfilment of the requirements for the Masters in Business Administration at Strathmore Business School, Strathmore University
Keywords: Private Label Brands; Economic factors; Strategic factors; Market factors; Influence; Supply; National brands; Manufacturers; Retailers; Kenya